Digital Book of Indonesian Rare Flora Using Augmented Reality: Buku Digital Flora Langka Indonesia Menggunakan Augmented Reality - Umami, Nur Reza; Dijaya, Rohman; Rahmawati, Yunianita (Procedia of Engineering and Life Science, 2023)
The uniformity of the flora is still not widely known. Therefore, natural knowledge has an important role in education considering the limitations of print media as a learning medium. Innovation by utilizing Augmented Realityp technology is very helpful as a learning medium that can support the learning process more effectively and efficiently, on the other hand Augmented Reality that displays 3D models of objects in real time can also increase interest in learning in knowing Indonesia's rare flora attractively and interactively.So, researchers designed and developed the application "Digital Flora Langka Indonesia Using Augmented Reality" with SDLC (Software Development Life Cycle) methods which are expected to help as an interesting learning medium.